A Scoping Review of Bacterial Vaginosis – A Silent but Potential Threat to Pregnancies and Gynecological Surgeries and Procedures - Ade-Ojo, Idowu; Abolarin, Esther; Okiki, Abimbola; Olufunke, Oso (British Journal of Healthcare and Medical Research, 2022)
Bacterial vaginosis (BV) is a common vaginal disorder in women of the reproductive age group that causes offensive vaginal discharge. BV occurs when Lactobacillus spp., the predominant species in healthy vaginal flora, are replaced by anaerobic bacteria, such as Gardnerella vaginalis. The prevalence is about 15-30% of women of reproductive age group. The reported risk factors include a high number of lifetime sexual partners, engagement in sexual intercourse at a younger age, practicing regular douching, and smoking. When BV occurs in pregnancy, there is an increased risk of preterm delivery and its associated complications. For decades, metronidazole has been the drug of choice for the treatment of BV, however, the rate of recurrence is as high as 50%. Therefore, prevention through lifestyle modifications will help to reduce the prevalence of BV.